Operational risk and its impact on non-performing loans in China - LI, WEI (2019)
Basel II and operational risk management have been introduced to China since 2004. However, there is still much room for improvement in risk management, as the effectiveness of the Basel Accord has been impacted by the underdeveloped market participants. Chinese banks focused more on profitability and overlooked the operational risk; as a result, violations of regulations and rules become prevalent in the banking sector. Compared with credit risk, operational risk has witnessed inadequate supervision for years, and it has been highlighted recently with an increasing number of penalties given by Chinese supervisors. Among penalty issues released from 2016 to 2018, multiple lines of evidence suggest that operational risk affects the non-performing loans (NPLs) level of a bank which has become the primary concern of Chinese regulators in the recent economic downturn and financial deleveraging. This essay investigates what impact does operational risk have on the NPLs ratio of Chinese commercial banks. An empirical analysis is provided based on penalty records of clients and process failure types of operational risk collected from the official website of China Banking and Insurance Regulatory Commission. The result indicates that commercial banks are managed to hide NPLs by taking the operational risk. A qualitative analysis of fraud-type operational risk is also provided to support the results of empirical models. Through illegal manipulation of loan disposal, loan quality classification and the policy of loan roll-over, more NPLs are hidden from financial reports. The findings suggest that undertaking operational risk helps banks achieve an illusion of excellent performance and high asset quality, which would damage the future sustainability of the whole financial system.